Canadian Public Opinion on Cannabis: How Far Out of Step With It Is the Existing Law? - Hathaway, Andrew D.; Erickson, Patricia G.; Lucas, Philippe (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2007)
Public attitudes in Canada are clecwly in fauour of loosening restrictions on cutnabis possession. opinion polls conducted oorcr the past few yems show that most Canadiars support decriminaliTing slmple possession cmd use of mmijtnna. Recent polls, moreo,uer, saggest that more than half faonw fuII legaliTation. Support for legal access for heabh pw’poses is higher; onll one in six adubs opposes this reform. National drug swueys offer few fwrher details beyond the demogral>hic profiles that relatc to certain uiews. This paper nkes a closer lnok at public opinion based on a random househokl survey of Toronto arluhs (N=1 ,081). This allows us to identify adlinonal characteristics associated with opinions about cmtnabis reform. Consistent with the findings from national drug surueys, the maiority opposes the cwtent prohibition. Respondents also recogniTed potential health concems in addition to aclnowledglng health benefits of ca.nabis and a uu.iety of problens with the existlng ktw. Public attitudes u’e broadly ’hcnm reduction’ oriented szggestlng euidence-based, public heahh initiatiq.les would. go:rp.er wide support as a uiable ahernatiq.te to qiminal conuols. R6sum6 Il ne fait auatn doute que les Cavhiens appuient le rel%oochement des restrictions concernant Ia possesslon de cannabis. Les sondages d’opinion men6s au cotns des demiires anndes rlotilent que In plupmt des Canadiens sont en fauern de la ddcriminalisation de la simp/r possession et de h consommation de ma’ijunna. De plus, des sc.tndages rlcents indiquent que plus dc lnmoiti| des Cawdiens appuientlabgalisation delamartiurma.IJn nomhe encore plus g|and de Cuvdiens appuient l’accd.s llgal d la marijwma pour des raisons de santd. Seul wl adulte srr siI s’oppos e d ln rdes mestues liglslatites. ks enqu rcs ncltionales sw la consommation de drogues fownissent seulement Etel4ues ren’ seignements de plw que les o[>inions de cernins groupes de personnes. Le pr€sent rapport udie plus d fond L’opinion du public d pctrtir d’m d.chmtillon aliatoire d’adultes de Toronto (n = 1 081). Cekt permet de cerner des cu’act1ristiErcs supplimenttires associ6es aux opinions concernu"Lt la rdforme des meswes liglslatives applicables au ccutnabis . Comme l’indiqtrcnt les rdsulnts des enqu tes nationales sru la consommation de drogwes , la ptupnt des reponfumts s’opposent d l’ interdiction actuelle . ils sont conscients des uou. bles de santd possibles, des bienfaits du cannabis pow lt santA et des probhmes causds par Ies lois en uigtettr. Dans I’ensemble,le public priuild.gie la . rdes mefaits , . Celn laisse croire qu’il rdserverait un accu.eil fauorable aux initiatiues de santd publique foncl1.es sw l.’expdrience clinique qui consntuent une solution de rechange qiable atu meswes de contrlle des actiuitds cwminelles.